Intraoperative robotic measurements of coronal alignment in total knee arthroplasty correlate with pre‐ and post‐operative long‐leg radiographs - Anoop S. Chandrashekar; Jacob A. Fox; Logan M. Locascio; Gregory G. Polkowski; Martin Faschingbauer; J. Ryan Martin (Journal of Experimental Orthopaedics)
Abstract Purpose This study sought to validate intraoperative robotic measurements of femoral and tibial component coronal alignment in total knee arthroplasty (TKA) by comparing to pre‐ and post‐operative standing, double stance, long‐leg radiographs (LLR). Methods This retrospective cohort study included 59 unique patients undergoing primary TKA at a single institution. Pre‐ and post‐operative femoral and tibial coronal alignment were measured on LLRs using a deep learning artificial intelligence model and compared to measurements obtained from the imageless robotic system to evaluate the robot's accuracy and reliability. Results Robotic measurements were highly correlated with measurements from preoperative LLR (Pearson r2 = 0.68). There was no significant difference in preoperative constitutional alignment between the two methodologies (p = 0.28). Additionally, the intraoperative and post‐operative alignment of femoral and tibial implants were not significantly different (p = 0.12 and p = 0.95, respectively) and were strongly correlated (Pearson r2 = 0.5 and Pearson r2 = 0.6 respectively). The mean difference in femoral alignment was 0.43° and the mean difference in tibial alignment was 0.01°. Conclusions The findings of this study suggest that there were no significant differences in the coronal alignment of TKA when assessed by a robotic system compared to LLR. This signifies the robotic system's high intraoperative accuracy and reliability in determining coronal alignment. Level of Evidence Level III.